2007
DOI: 10.3928/01484834-20070301-05
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Nursing Students' Knowledge of and Attitudes Toward Aging: Comparison of Context-Based Learning and a Traditional Program

Abstract: <h4>ABSTRACT</h4> <P>The purpose of this study was to investigate nursing students’ knowledge of and attitudes toward older adults in the first and fourth years of a baccalaureate program, following the introduction of a context-based learning (CBL) curriculum, and to compare the fourth-year CBL student findings to those of fourth-year students in the final year of the traditional, lecture-based baccalaureate program. The Facts on Aging Questionnaire was used to assess knowledge, and the Agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 31 publications
6
41
2
1
Order By: Relevance
“…This finding may have been influenced by the combination of theory and clinical in the integrated course, providing students with the ability to apply their new knowledge in practice settings. Similarly, other scholars indicated improvements in both knowledge and beliefs among students in a gerontological course that included theory and practice components (Lange et al 2006, Williams et al 2007, albeit these courses did not integrate adult and older adult content, an important distinction of the current study.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…This finding may have been influenced by the combination of theory and clinical in the integrated course, providing students with the ability to apply their new knowledge in practice settings. Similarly, other scholars indicated improvements in both knowledge and beliefs among students in a gerontological course that included theory and practice components (Lange et al 2006, Williams et al 2007, albeit these courses did not integrate adult and older adult content, an important distinction of the current study.…”
Section: Discussionmentioning
confidence: 59%
“…A key point of contention in the literature is the type of clinical setting for students to learn about older adult care. Although some have argued that the frequent practice of assigning students to LTRC settings for their first clinical experiences can give the impression that older adult care is simple, and that these clinical experiences have the potential to leave nursing students with negative impressions of older adult care (Aud et al 2006, Holroyd et al 2009, Ironside et al 2010, others have suggested that these environments can be a positive place for senior level students to learn about the complexity of older adult care, offering opportunities to integrate theory and clinical learning through focused assessments and interactions with interdisciplinary teams (Williams et al 2007). Most students learn about older adult care in acute hospital environments.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…To assess self-efficacy and knowledge related to prescription and over-the-counter drug interactions of students (46) Knowledge about medication Specialist knowledge required in nursing older people Knowledge significant differences regarding learning outcomes between the curricula in terms of the organisation of education (22), the content and the timing of teaching (33,67) or the delivery of the curricula (68). Regarding the teachers' competence, nursing degree programmes reported having insufficient numbers of teachers with qualifications in nursing older people (e.g.…”
Section: Attitudesmentioning
confidence: 99%
“…11,12 Overall, the educational interventions used for nursing, medical, dental, and allied health students to date have had little to no effect on improving their general attitudes towards older adults. [27][28][29] Several investigations have studied the preexisting attitudes and beliefs that students may bring with them to school. Incoming students in both medicine and nursing have been surveyed to measure their knowledge and attitudes about older people.…”
Section: The Development Of Attitudes Beliefs and Behaviorsmentioning
confidence: 99%